www.bazaar4lokal.shop A Web-Based Platform for Local Businesses - Mohamad Ariff, Nur Dianah (IRC, 2020)
What is a local business? The term ‘local’ means a particular geographical area near to your neighbourhood. A local business is any company operating to provide products or goods and services to the customers in a local population, city, or geographic area.